2014
DOI: 10.1515/jpem-2013-0296
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of adropin and leptin levels in pediatric obesity-related nonalcoholic fatty liver disease

Abstract: In this study, serum adropin levels were significantly lower in obese adolescents with fatty liver disease compared to patients without fatty liver disease and healthy controls. Lower adropin level was an independent risk factor for NAFLD in obese adolescents in logistic regression analysis. Assessment of serum adropin concentrations may provide a reliable indicator of fatty liver disease in obese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 13 publications
2
57
0
Order By: Relevance
“…Reduced levels of adropin have been observed in obesity-associated insulin resistance, gestational diabetes, nonalcoholic fatty liver disease (NAFLD), acute myocardial infarction, coronary atherosclerosis and endothelial dysfunction [7,8]. Sayin et al have demonstrated that low adropin concentrations were associated with the risk of NAFLD (18). It should be stressed, however, that their study involved children and not adults.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced levels of adropin have been observed in obesity-associated insulin resistance, gestational diabetes, nonalcoholic fatty liver disease (NAFLD), acute myocardial infarction, coronary atherosclerosis and endothelial dysfunction [7,8]. Sayin et al have demonstrated that low adropin concentrations were associated with the risk of NAFLD (18). It should be stressed, however, that their study involved children and not adults.…”
Section: Discussionmentioning
confidence: 99%
“…Correlations between circulating adropin levels and different pathophysiological states in mice and humans have been reported (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). In brief, the circulating concentration of adropin was reduced markedly in several metabolic diseases, including obesity-associated insulin resistance (1,5,11); obesity-related, nonalcoholic fatty liver disease (11); gestational diabetes mellitus (7); and endothelial dysfunction (6,8,14). However, conversely, other studies found that plasma adropin levels in humans were not correlated inversely with obesity on the basis of body mass index (6,8,13) or with endothelial dysfunction (9).…”
mentioning
confidence: 99%
“…In literature, there are recent studies that suggest the existence of an association between adropin, and obesity and IR (1,3,9). Based on our findings, however, while a difference was present in lipid profiles and HOMA-IR values of controls and patients, consisting of children with obesity and MetS, the absence of such a difference between adropin levels of patient and control groups, and of a correlation between adropin, and weight and HOMA-IR suggested that no association is present between adropin, and obesity and IR.…”
Section: Discussionmentioning
confidence: 99%